Handbook of Human Factors and Ergonomics 2006
DOI: 10.1002/0470048204.ch47
|View full text |Cite
|
Sign up to set email alerts
|

Online Communities

Abstract: Pete Bradshaw [1]"Our online community provides a dynamic forum for you to discuss current topics and concerns with the wider education community."This quote is taken from the Teachernet website [2], but could be claimed to apply to any number of education sites. Increasingly, online content is being complemented by with opportunities for readers to interact with each other or participate in debate. This article will look at the proliferation of such 'online communities'. It will consider how they might be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that most members of health support and education support communities accept lurkers as members of the community (Abras, 2003; Maloney-Krichmar, 2003), suggesting that the process of lurking is not disruptive to the group process. Consequently, it appears that people intuitively engage in a process of matching their characteristics with those of potential group members without being instructed to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that most members of health support and education support communities accept lurkers as members of the community (Abras, 2003; Maloney-Krichmar, 2003), suggesting that the process of lurking is not disruptive to the group process. Consequently, it appears that people intuitively engage in a process of matching their characteristics with those of potential group members without being instructed to do so.…”
Section: Discussionmentioning
confidence: 99%